2006
DOI: 10.1017/s0016774600021405
|View full text |Cite
|
Sign up to set email alerts
|

Integrated chronostratigraphy of the Pliocene-Pleistocene interval and its relation to the regional stratigraphical stages in the southern North Sea region

Abstract: Time-stratigraphic interpretations of Late Pliocene to Early Pleistocene sediments from onshore locations and from marginal marine settings of the North Sea Basin often refer to the subdivision of the Dutch and British ’Quaternary’ regional stratigraphic stages. Since age control for these stages and their stage boundaries are based on relative dating methods, in this study pollen, dinoflagellate cysts and foraminiferal assemblages were investigated to correlate the regional stratigraphic stages independently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 36 publications
2
37
1
Order By: Relevance
“…Sea surface temperature estimates based on 5 18 0 ratios indicate very low temperatures of 4.5 -8.3° C. This contradicts temperature estimates based on dinocysts from our samples as well as previous estimates for the southern North Sea Basin during the Early Pliocene, that show higher than modern values (Johnson et al, 2000;Kuhlmann et al, 2006). Johnson et al (2000), comparing growth increment lengths and stable isotope values of both modern and Zanclean Aequipecten opercularis, concluded that cryptic diagenesis caused these aberrant isotope Netherlands Journal of Geosciences -Geologie en Mijnbouw | 87 -2 N G estimates.…”
Section: Sea Surface Temperatures (Sst)contrasting
confidence: 99%
See 1 more Smart Citation
“…Sea surface temperature estimates based on 5 18 0 ratios indicate very low temperatures of 4.5 -8.3° C. This contradicts temperature estimates based on dinocysts from our samples as well as previous estimates for the southern North Sea Basin during the Early Pliocene, that show higher than modern values (Johnson et al, 2000;Kuhlmann et al, 2006). Johnson et al (2000), comparing growth increment lengths and stable isotope values of both modern and Zanclean Aequipecten opercularis, concluded that cryptic diagenesis caused these aberrant isotope Netherlands Journal of Geosciences -Geologie en Mijnbouw | 87 -2 N G estimates.…”
Section: Sea Surface Temperatures (Sst)contrasting
confidence: 99%
“…Louwye et al (2004) show that the last occurrence of M. choanophorum is associated with the Kruisschans Member in Belgium. Kuhlmann et al (2006) show that the L0D of Barssidinium spp. falls within the Piacenzian (circa 2.6 Ma).…”
Section: Unit C (Samples 7 -11 M)mentioning
confidence: 94%
“…The chronostratigraphy of Kuhlmann et al (2006) in Dutch exploration well A15-03 (55°18′N, 3°48′E; Fig. 1) can be correlated to the work of Köthe (2007Köthe ( , 2012 and Thöle et al (2014) in the German sector of the North Sea, Nielsen et al (2008) and Rasmussen et al (2005) in the Danish sector, and Noorbergen et al (2015) onshore Netherlands (Table 1; Harding 2015).…”
Section: Chronostratigraphic Calibrationmentioning
confidence: 71%
“…The base Quaternary stratigraphic surface, taken as 2.58 Ma, was correlated to a well-defined and continuous seismic reflection trough using the Dutch North Sea well A15-03, for which very detailed bio-and magneto-stratigraphic dating is available in the public domain (Kuhlmann et al 2006; see discussion below). The horizon was picked at the well tie and then mapped down the depositional dip of the clinoforms into the basin, which minimized correlation errors to about half the dominant wavelength (20 -35 m), using a diminishing grid size (200 m then 100 m then 50 m), which was then propagated in full three dimensions (Hart 1999).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation